Preliminary Screening of Dalbergia sissoo Seedlings from Different Seed Sources for Resistance to Defoliator Plecoptera reflexa Gue (Lepidoptera : Noctuidae) - Meshram, P. B.; Jain, Avinash; Gera, Mohit (Indian Forester, 1999)
Dalbergia sissoo seedlings from nine different seed sources were screened against defoliator, Plecoptera reflexa Gue. It was observed that Kanpur (U.P.) origin exhibited maximum resistance closely followed by Khoshala (Orissa) seed source. The performance of the origin was relatively better in all five parameters viz. damage seedlings, leaves, leaf area consumed, larval population and chemical analysis (Polyphenol, protein, phosphorus, calcium and potassium).